2012
DOI: 10.1128/aac.00519-12
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Derived Dimer Diphenyl Phosphate Is an Irreversible Inhibitor of Human Cytomegalovirus Replication

Abstract: ABSTRACTWe previously reported that among a series of artemisinin-derived monomers and dimers, dimer diphenyl phosphate (838) was the most potent inhibitor of human cytomegalovirus (CMV) replication. Our continued investigation of a prototypic artemisinin monomer (artesunate [AS]) and dimer (838) now reveals that both compounds have specific activity against CMV but do not inhibit lytic replication of human herpesvirus 1 or 2 or Epstein-Barr virus. AS and 838 inhibited CMV repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…We identified the best dimer in CMV inhibition to be the dimer diphenyl phosphate (DPP; molecular weight [MW], 838; referred to as dimer 838). Dimer 838 proved to have unique anti-CMV activities even compared to those of other artemisinin-derived dimers, including irreversible inhibition of CMV replication and the ability to inhibit virus replication even when added to human fibroblasts prior to infection (12). Our continued work further reveals the characteristics of dimer 838 and delineates its improved anti-CMV activities compared to those of other artemisinin-derived dimers.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…We identified the best dimer in CMV inhibition to be the dimer diphenyl phosphate (DPP; molecular weight [MW], 838; referred to as dimer 838). Dimer 838 proved to have unique anti-CMV activities even compared to those of other artemisinin-derived dimers, including irreversible inhibition of CMV replication and the ability to inhibit virus replication even when added to human fibroblasts prior to infection (12). Our continued work further reveals the characteristics of dimer 838 and delineates its improved anti-CMV activities compared to those of other artemisinin-derived dimers.…”
mentioning
confidence: 73%
“…We reported that artemisinins are early inhibitors of CMV replication. When dimer 838 was removed at 12 hpi, it had already achieved nearly complete CMV inhibition, while AS required longer than 40 h to achieve the same effect on CMV replication (12). To address whether the pattern of dimer 838 removal was a result of its dimer backbone or DPP, an add-on and removal assays were performed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AS cannot form a dimer, but chemical synthesis resulted in several artemisinin-derived dimers, including dimer 606. Studies describing the anti-CMV activity of AS and dimer 606 have shown that the latter was significantly more active than AS, much more than two units of monomers combined (9,16,17). The compounds were dissolved in dimethyl sulfoxide (DMSO), and stocks of 10 mM were stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…We reported that the CMV inhibitors artemisinins and cardiac glycosides acted earlier than GCV in CMV-infected cells, and limited combination studies indicated that GCV plus artemisinins had synergistic activities, while GCV plus digoxin showed only additive effects on CMV inhibition (23,24). We now report a comprehensive analysis of multiple drug combinations.…”
mentioning
confidence: 99%